New treadmill design for energy harvesting - Mustafa F.F.; Hussein O.; Daham S.R.; Sabry A.H. (Bangladesh University of Engineering and Technology, 2023)
Recently, increasing pollution around the world as a result of the increased demand for energy is an essential and critical issue that people face nowadays. As a result of this, there was an increase and an urgent need to produce electricity from its clean sources. The process of producing clean energy is one of the necessary steps to reduce pollution around the world in addition to the possibility of maximizing the resources of institutions by reducing the depletion of different resources to produce the energy that humans need in various directions. This paper aims to convert the kinetic energy generated from walking and running people into electrical power. It can carry out with a brilliant output by the implementation of a new treadmill system with gears. The idea of this system summarizes by the conversion of human walking force using gears and duplicate the overall rotational speed which connected with a generator to produce electricity. Experiments of the clean energy production carried out using the treadmill system with gears and the electric power generated as a result of walking and running. Also, a comparison between the production of clean energy calculated once using the regular treadmill and once using the proposed system (treadmill system with gears). With applying of the new design of the treadmill system with gears in Sport and Health center with ten machines a 500 kw yearly would obtain from one center which can increase the energy production and reduced the percentage of pollution. 2020 Zibeline International Publishing Sdn. Bhd.. All rights reserved.